2024
DOI: 10.3390/ma17061335
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Tribofilm Formation in Boundary Lubrication Investigated Using In Situ Measurements of the Friction Force and Contact Voltage

Anna E. Tsai,
Kyriakos Komvopoulos

Abstract: The complex dynamics of tribofilm formation on boundary-lubricated steel surfaces were investigated in real time by combining in situ measurements of the temporal variation of the coefficient of friction and contact voltage. Sliding experiments were performed with various blends consisting of base oil, zinc dialkyl dithiophosphate (ZDDP) additive, and two different dispersants at an elevated oil temperature for a wide range of normal load and fixed sliding speed. The evolution of the transient and steady-state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…The ball-on-disk tribometer (Falex-6, thrust washer, Bruker Co., Billerica, MA, USA) used in a previous study of the friction characteristics of tribofilms formed from similar blends [38] was also used to perform the wear experiments of this study. Both the ball and disk specimens consisted of AISI 52100 steel (1.04 C, 0.35 Mn, 0.275 Si, 1.45 Cr, and 96.89 Fe, all wt%).…”
Section: Specimens and Wear Experimentsmentioning
confidence: 99%
See 4 more Smart Citations
“…The ball-on-disk tribometer (Falex-6, thrust washer, Bruker Co., Billerica, MA, USA) used in a previous study of the friction characteristics of tribofilms formed from similar blends [38] was also used to perform the wear experiments of this study. Both the ball and disk specimens consisted of AISI 52100 steel (1.04 C, 0.35 Mn, 0.275 Si, 1.45 Cr, and 96.89 Fe, all wt%).…”
Section: Specimens and Wear Experimentsmentioning
confidence: 99%
“…The wear experiments were carried out under conditions of different loads in the range of 1.22-10.15 kg (i.e., 11.97 to 99.57 N), or mean Hertzian contact pressures in the range of 0.785-1.589 GPa (computed for 193 GPa elastic modulus, 0.3 Poisson's ratio, and 8 cm ball diameter), oil temperature of 100 ± 5 • C, linear sliding velocity fixed at 0.19 m/s, and test time set at 2 h. Calculations confirmed that the foregoing test conditions resulted in sliding in the boundary lubrication regime. Further details about the properties, polishing, and cleaning of the specimens can be found elsewhere [38].…”
Section: Specimens and Wear Experimentsmentioning
confidence: 99%
See 3 more Smart Citations